Education in Colombia: market dynamics and globalization - Rubiano Aldana, Diego Alejandro; Beltrán Jiménez, Harold (Cooperativismo & Desarrollo, 2016)
Purpose: To present a reflection and construct an interpretation from the perspective of the historical hermeneutic paradigm in order to generate processes of understanding about the social phenomenon of the commodification of education. Description: Education in Colombia has been recognized as a fundamental right since the constitutional reform of 1991. However, the recognition process has been accompanied by the advent of new information and communications technologies. E-learning, together with the franchise system, have formed a business model that is presented as an alternative and a strategy for economic development in the country’s education market. Viewpoint: This relationship has influenced the guarantee of the right to education by linking access and quality to economic opportunities. Conclusions: In Colombia, the education project of the country continues to depend on circumstances. Planning in the medium and long term is not part of a coherent public policy because there are always other priorities in budget allocation. In an unequal country like Colombia, this has meant turning education into a factor that increases inequality instead of what it should be: a factor of equality.